Gingival Squamous Cell Carcinoma and the Importance of Early Diagnosis in Treatment Outcome: A Clinical Case Report - Maryam Koopaei; Abbas Karimi; Monir Moradzadeh Khiavi (Journal of Kerman University of Medical Sciences, 2021)
Background: Gingival SCC is the malignancy of gingival epithelium. Prevalence of gingival and alveolar process SCC is 2% to 12% of diagnosed cases. However, it occurs much more frequently in the mandible than in the maxilla. The purpose of this case report is to introduce a case of gingival SCC in the anterior maxilla with no diagnosed risk factor.Case report: A 49-year- old male with the chief complaint of a growing mass in anterior maxillary gingiva with the differential diagnosis of reactive lesions for three months. Panoramic and periapical examination showed no evidence of generalized alveolar bone resorption. After the excisional biopsy, in the follow-up session, the recurrence of the lesion was seen. Considering rapidly growth of the lesion, suspension to SCC was reinforced and the next excisional biopsy was done. Histopathologic analysis established the diagnosis of squamous cell carcinoma.Conclusion: SCC is a great imitator; for lesions with a benign appearance on the gingiva and it should be considered in the differential diagnosis. This case report revealed the importance of early diagnosis of gingival SCC. Considering the low survival rate of gingival SCC and its high morbidity, early diagnosis help improves the survival of the patient